USER SITTING BEHAVIOR ANALYSIS ALUN-ALUN BANDUNG SHELTER - Galuh Damayanti; Terinza Terinza; Asmahan Fakhr; Irwan Sudarism (Ide dan Dialog Desain Indonesia (Idealog), 2022)
The bus stop is one of the public facilities used by the public to wait for buses or public transportation. One of the bus stops in the city of Bandung, namely the Bandung Square Bus Stop, which has an area of about ± 100 m², is a bus stop that is quite often used by the public, especially since it is located in the center of Bandung. This bus stop is used by various age groups, with sitting behaviors such as being near or far from other users, waiting standing up, and users sitting at sign names. The variety of user behavior while waiting for the bus creates space at the Bandung Square Bus Stop. The purpose of this research is to find out what factors influence the sitting behavior of bus stop users which can then be used as a solution in the design of the bus stop. This research is a form of further research conducted by Aria Dirgantara Putra, Muhammad Azwir, Vera Octaviany, and Rasty Nilamsuci in their journal "Study of Transformation of Form and Function of Bandung Square as Public Open Space". To find out, the method used in this study is a qualitative method. Where the qualitative research method is carried out by means of observation observations and behavior mapping (behavior mapping) and is equipped with additional data through visitor questionnaires. Based on the results of processing the data that has been collected, it can be concluded that the behavior of users while waiting for the bus has a dif erent style according to the comfort of the users themselves from various circles. Keywords: bus stop, behavior mapping, sitting behaviors